Perception of Barbell Velocity: Can Individuals Accurately Perceive Changes in Velocity? - Shaw, M.; Thompson, S.; Myranuet, P.; Tonheim, H.; Nielsen, J.; Steele, J. (International Journal of Strength and Conditioning, 2023)
The aim of the study was to investigate whether resistance-trained participants can accurately predict changes in barbell velocity, specifically in the dead- lift exercise, without feedback from velocity monitoring devices. Seventeen participants (16 male, 1 female; age = 24.7 ± 3.8) were randomized in a counterbalanced, crossover design two experimental sessions that consisted of three sets of Deadlift at 60-and-80% one-repetition maximum (1RM). The number of repetitions were determined by the participants as they were asked to terminate each set when they felt the barbell velocity had reduced by 20%, relative to repetition one. A binomial mixed effects regression model was used to assess the accuracy of participants ability to stop after reaching at least 20% velocity loss. Participants tended to underestimate their proximity to 20% velocity loss and thus had relatively low probability of correctly stopping after reaching this threshold. There was only a 10.49% probability that people could perceive at least 20% velocity loss greater than chance (i.e., 50% probability). Our data, suggests that most participants cannot accurately perceive changes in velocity without exposure to augmented feedback.